A new method for right ventricular lead implantation into the intraventricular septum. (19th May 2022) - Narumi, T; Naruse, Y; Kaneko, Y; Sano, M; Urushida, T; Maekawa, Y
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Right ventricular (RV) lead placement into the interventricular septum is only accurate in 16–48% of cases under conventional fluoroscopic guidance. A previous report showed the importance of individualized left anterior oblique (LAO) projection to improve the success rate of RV lead placement into the interventricular septum. However, this procedure is complicated. We sought to investigate the preprocedural predictors of individualized LAO projection. Methods: We assessed the relationship between preoperative electrocardiographic parameters and the angle of the interventricular septum obtained using thoracic computed tomography (CT). Results: In the retrospective derivation cohort group (n=39), the mean angle of individualized LAO assessed by thoracic CT was 53.1±8.9°, and the preoperative electrocardiogram QRS axis was strongly correlated with the interventricular septum axis detected by thoracic CT (R2 = 0.490). In contrast, the preoperative electrocardiographic transitional zone was not associated with the interventricular septum axis (R2 = 0.041, P = 0.78). Using individual LAO projection derived from the preoperative electrocardiogram QRS axis, it was confirmed that the RV lead was placed in the interventricular septum during the pacemaker procedure in the prospective internal validation group (n=30). The success rate for placing the RV lead into the interventricular septum was significantly improved in the internal validation cohort group (93% vs. 64%, P < 0.05). In addition, the N-terminal pro-brain natriuretic peptide level decreased significantly after surgery in the interventricular septal indwelling group. Conclusions: Individualized LAO angle derived from the preoperative electrocardiogram QRS axis is a new useful and simple method for RV lead implantation into the interventricular septum.